Analysis of the Phenomenon of Searle's Model of Illocutionary Speech Acts in A Movie Titled “Babysitter yang Tertukar”: A Pragmatics Study - Zidan Rizka Alhafidz (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
This paper discusses research on the phenomenon of illocutionary acts according to Searle's model, using the film “Babysitter yang Tertukar” as the research object. The method used in this research is a descriptive qualitative method with techniques for collecting data, analyzing data, describing, and finally drawing conclusions. The research results reveal that five types of Searle's illocutionary acts are present in the film as a whole. The purpose of this research is to describe the speech acts in the film “Babysitter yang Tertukar”. This research provides benefits to enhance knowledge about the use of illocutionary acts and to identify the categories of types used.